Sociocultural Values In 2nd Intermediate Textbook "English For Iraq" - et. al., Huda Abdul Razzaq , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to evaluate socio-cultural values included in English textbooks for the 2nd intermediate class in Iraq and to show the types of cultures that appear in the English textbooks for the 2nd intermediate class in Iraq. Is it target culture, source culture, or international culture? For this purpose, a checklist has been drawn from Brook's list of sociocultural references to analyze the content of the Pupil’s Book and Activity Book of English for Iraq 2nd Intermediate. The socio-cultural values include social references, historical references, and geographical references. After analyzing the Pupil’s Book and Activity Book of English for Iraq 2nd intermediate, the results reveal that sociocultural values are mainly based on the International culture. The source culture is dominating over the target culture.